Reducing Hemodynamic Compromise with Placental Removal at 10 versus 15 Minutes: A Randomized Clinical Trial - Magann, Everett F.; Niederhauser, Amy; Doherty, Dorota A.; Chauhan, Suneet P.; Sandlin, Adam T.; Morrison, John C. (American Journal of Perinatology, 2012)
Objective To determine if hemodynamic compromise can be reduced with manual placental removal at 10 compared with 15 minutes.Study Design Singleton pregnancies admitted for delivery with no contraindication to a vaginal delivery were randomized to a 10-minute group (placentas manually removed if not spontaneously delivered by 10 minutes) versus a 15-minute group. The primary outcome, hemodynamic compromise, was defined as: blood loss exceeding 1000 mL and/or circulatory instability (inability to maintain blood pressure/pulse secondary to acute blood loss) and/or drop in hematocrit of ≥10 percentage points.Results From July 2006 to July 2010, 156 women were randomized into the 10-minute group and 156 in the 15-minute group. Women in the 15-minute group had a greater likelihood of hemodynamic compromise univariately (19.2% versus 6.4%, p = 0.001) and after adjustments for ethnicity, induction rate, duration of second stage of labor, and nulliparity (relative risk 3.03, 95% confidence interval 1.52 to 5.47, p = 0.002).Conclusion Hemodynamic compromise is decreased with manual placental removal within 10 minutes of delivery compared with 15 minutes.
Keywords: manual placental removal; postpartum hemorrhage; hemodynamic compromise; third stage of labor